2021
DOI: 10.1002/tesj.612
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between two measures of L2 phonological vocabulary knowledge and L2 listening comprehension

Abstract: Research addressing the relationship between vocabulary knowledge and second language (L2) listening comprehension has been conducted mostly using measures that tap orthographic vocabulary knowledge. The few studies that have used measures that tap phonological modality to delineate the relationship between vocabulary and L2 listening have focused on either the receptive or productive dimension of vocabulary knowledge, but not both. To advance knowledge on this matter, this study investigated the degree to whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Learners who have difficulty recognizing known words when listening without reading may benefit from more systematic attention to the sounds of English starting at the lexical level before proceeding to phrasal level as well as marked forms of prosodic meaning. Masari (2022) investigated the effects of phonological vocabulary knowledge in correlation with L2 listening comprehension and found that productive phonological vocabulary knowledge correlated most strongly with L2 listening (r = .74). Therefore, curriculum designs that only require learners to memorize word meanings and spellings but not their phonological counterparts may be of disservice to learners (Lacroix & Castle, 2019;Nation, 2001;Siegel, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Learners who have difficulty recognizing known words when listening without reading may benefit from more systematic attention to the sounds of English starting at the lexical level before proceeding to phrasal level as well as marked forms of prosodic meaning. Masari (2022) investigated the effects of phonological vocabulary knowledge in correlation with L2 listening comprehension and found that productive phonological vocabulary knowledge correlated most strongly with L2 listening (r = .74). Therefore, curriculum designs that only require learners to memorize word meanings and spellings but not their phonological counterparts may be of disservice to learners (Lacroix & Castle, 2019;Nation, 2001;Siegel, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…A test is an instrument to measure an individual’s knowledge, ability, or performance in a specific domain such as the vocabulary taught in a specific lesson (Brown & Abeywickrama, 2010 ). Being alert about the format of the test, test-takers can respond to the items less demandingly (Masrai, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emotions-excitement and the ability to judge the behavior of themselves and others and make decisions based on these judgments-are just some of these God-given characteristics that it has made human responsibility heavier [20,21]. Specialists in various sciences, especially psychologists, sought to create a comprehensive concept that includes all communication patterns and techniques for cultivating these patterns in all areas of human life to increase people's efficiency and ability [22,23]. ese efforts led to the invention of the concept of emotional intelligence.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Previous studies in the world (e.g., [7,[17][18][19]) have indicated that learners have difficulty in understanding the meaning of some words in a given text to the effect that they fail altogether to comprehend the importance of the text itself. In response to this problem, this study focused on how to enhance the vocabulary knowledge of Saudi EFL learners.…”
Section: Introductionmentioning
confidence: 99%